(untitled) (Journal of Applied Oral Science, 2015)
Objective The current study aimed to investigate the β-catenin expression in oral leukoplakia (OL) with different degrees of epithelial dysplasia and normal oral mucosa.Material and Methods Formalin-fixed, paraffin-embedded tissue samples of 39 OL (mild dysplasia n=19, moderate dysplasia n=13, and severe dysplasia n=7), and 10 normal oral mucosa (control group) were submitted to immunohistochemical reactions to anti-β-catenin primary antibody. A qualitative β-catenin analysis was performed based on the percentage of positive cells. The cellular location and the epithelial layer were also considered. The Chi-square test and the Fisher’s exact test were used to verify possible differences in the β-catenin expression among the OL groups. A p-value of